Gestión de riesgos en contratos de construcción. Propuesta para reducir plazos y costos, año 2019 - Soto Ruben , Gómez Sánchez (2022)
It is in the national interest to solve the public problem that arises as a result of the gaps in existing infrastructure in the country; Therefore, it is natural that the formulation of public investment projects is necessary to make viable, design and execute works aimed at solving such an important problem. But as detailed in the present investigation, the execution of such public works is subject to the effects of typical risks that translate into longer terms and costs, increasing the confusion of the population affected by such an important public problem. The research carried out allows us to verify that “The application of risk management in construction contracts within the framework of public policies has a direct impact on reducing bad practices in terms of deadlines and costs in the execution of works in the construction sector in Peru, year 2019”. Based on this verification, several actions can be defined in the different sectors involved and also foresee other investigations on the training of professionals related to the formulation, design and execution of public works.